A human respiratory tract-associated bacterium with an extremely small genome - Fukuda, Kazumasa (Commun Biol, 2021)
Recent advances in culture-independent microbiological analyses have greatly expanded our understanding of the diversity of unculturable microbes. However, human pathogenic bacteria differing significantly from known taxa have rarely been discovered. Here, we present the complete genome sequence of an uncultured bacterium detected in human respiratory tract named IOLA, which was determined by developing a protocol to selectively amplify extremely AT-rich genomes. The IOLA genome is 303,838 bp in size with a 20.7% GC content, making it the smallest and most AT-rich genome among known human-associated bacterial genomes to our best knowledge and comparable to those of insect endosymbionts. While IOLA belongs to order Rickettsiales (mostly intracellular parasites), the gene content suggests an epicellular parasitic lifestyle. Surveillance of clinical samples provides evidence that IOLA can be predominantly detected in patients with respiratory bacterial infections and can persist for at least 15 months in the respiratory tract, suggesting that IOLA is a human respiratory tract-associated bacterium.